ACHIEVING ENVIRONMENTAL PERFORMANCE THROUGH ENVIRONMENTAL MANAGEMENT ACCOUNTING AND INDIVIDUAL FACTORS: A LITERATURE BASED VIEW - Rahajeng, Lila Widya; Realita, Tasnim Nikmatullah; Firdaus, Rizalnur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study reviews the recent literature on the relationship between Environmental Management Accounting (EMA), Organizational Citizenship Behavior for the Environment (OCBE), and Environmental Performance (EP). Using the literature review approach, empirical peer-reviewed articles published between 2020 and 2025 were systematically identified, screened, and analyzed. A qualitative synthesis was conducted focusing on research objectives, methodologies, variables studied, contexts, and key findings. The review reveals that EMA functions not only as an accounting tool but also as a strategic enabler that, particularly when combined with human resource and managerial practices, stimulates OCBE and thereby improves EP. OCBE consistently emerges as a mediating mechanism that translates organizational systems into pro-environmental behaviors and performance outcomes, while EP contributes to corporate reputation, social legitimacy, and competitive advantage.